Anne B. Turpeau papers - Turpeau, Anne B. (Anne Brock), 1924-
Correspondence, memoranda, speeches, writings, studies, reports, project proposals, organizational minutes and agenda, conference and committee records, legal documents, appointment calendars and notebooks, biographical records, Brock and Turpeau families papers, press releases and statements, newspaper clippings, printed material, and other papers relating to Turpeau's public service and activism on behalf of civil rights, community development, and women's rights. Includes material pertaining primarily to her service with the Washington Urban League, Washington, D.C., (1965-1972); District of Columbia Commission for Women (1976-1979); International Women's Decade, 1976-1985; D.C. International Women's Year Coordinating Committee (1977-1978); National Women's Conference (1977); and the U.S. Delegation to the World Conference of the United Nations Decade for Women, Copenhagen, Denmark (1980). Also documents her work with the Black Women's Agenda, National Council of Negro Women, Organization of Black Activist Women, and Washington Women's Forum. Topics from her years with the Washington Urban League include crime prevention, housing assistance, job training, urban renewal projects, and the legal battle over utility company deposits.
Social activist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brock family; Turpeau family; District of Columbia. -- Commission for Women; United States. -- Delegation to the World Conference of the United Nations Decade for Women: Equality, Development, and Peace, 1980, Copenhagen, Denmark; D.C. International Women's Year Coordinating Committee; Black Women's Agenda; International Women's Decade, 1976-1985.; National Council of Negro Women; Organization of Black Activist Women; Washington Urban League; Washington Women's Forum; African American women -- Societies and clubs; Civil rights; Civil rights -- Washington (D.C.); Community development; Community development -- Washington (D.C.); Crime prevention; Housing; Occupational training; Public utilities; Urban renewal; Women -- International cooperation; Women -- Societies and clubs; Women's rights; Women's rights -- Washington (D.C.); Social activist